Hubungan Dukungan Suami Dengan Proses Adaptasi Psikologis Pada Ibu Nifas - Junika, Irna Rara; Sulistyoningtyas, Sholaikhah (Politeknik Kesehatan Kementrian Kesehatan Semarang, 2025)
The postpartum period is a transition period that is full of challenges for mothers, both physically and psychologically. Many postpartum mothers experience anxiety, stress, and even postpartum depression, which can negatively affect the mother’s health and the baby’s development. Husband's support is an important factor in helping mothers adapt psychologically during the postpartum period. Objective of the study is to determine the relationship between husband's support and the psychological adaptation process in postpartum mothers at PKU Muhammadiyah Gamping Hospital. Method in this research used quantitative methods with a cross-sectional design. The sample of this study consisted of 30 postpartum mothers selected using the total sampling technique. Data was collected through a questionnaire consisting of variables of husband's support and psychological adaptation of postpartum mothers, then analyzed using the Chi-Square test. The results tested using the Chi-Square statistical test showed a significance value (2-tailed) of 0.000 (p < 0.05). Thus, Ho was rejected and Ha was accepted, meaning that there is a relationship between husband's support and the psychological adaptation of postpartum mothers at RS PKU Muhammadiyah Gamping. In addition, the correlation coefficient value of 0.707 shows that the relationship between husband's support and postpartum psychological adaptation of mothers is strong. There is a significant relationship between husband's support and psychological adaptation in postpartum mothers at PKU Muhammadiyah Gamping Hospital. Suggestion is hospitals can improve education and counseling for husbands to better support the psychological well-being of postpartum mothers.